Rancangan User Interface/User Experience Pelacakan Hasil Panen Serai Wangi Menjadi Minyak Menggunakan Metode Design Sprint - Putri Winly Apriliani; Pristi Sukmasetya (Journal of Information System Research (JOSH), 2023)
The development of technology in the digital era can now be used to do business with the help of technology. The system can be visualized through UI(User Interface)/UX(User Experience). One method to do UI/UX is to use the design sprint method. With the form of system visualization, it can make it easier for Users or business actors to run a business, especially in tracking systems. The main focus of this research is to design the design of a system that uses the yield of citronella yields into petroleum design sprint. The results of the design will be tested for potential Users to get the test results from the application design that has been made. Having a tracking system in the process helps lemongrass entrepreneurs in monitoring the ongoing process. This reduces the incidence of citronella in the event of an accident or accident during the direct oil production process. In the test using the help of maze with a click error value in Scenario 1 (User tries to register) of 33.3%, Scenario 2 (User makes a harvest order) of 16.7% and Scenario 4 (User tries to add a bank account) while for Scenario 3 (User tries adding the address of the garden), Scenario 5 (User sees info about going orders) and Scenario 6 (User completes the harvest process by payment using QR) there is no click error when Usability takes place.